2022
DOI: 10.3390/pharmaceutics14010130
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy of Liposomal Formulations Containing Tobramycin and N-Acetylcysteine against Tobramycin-Resistant Escherichia coli, Klebsiella pneumoniae, and Acinetobacter baumannii

Abstract: The antibacterial activity and biofilm reduction capability of liposome formulations encapsulating tobramycin (TL), and Tobramycin-N-acetylcysteine (TNL) were tested against tobramycin-resistant strains of E. coli, K. pneumoniae and A. baumannii in the presence of several resistant genes. All antibacterial activity were assessed against tobramycin-resistant bacterial clinical isolate strains, which were fully characterized by whole-genome sequencing (WGS). All isolates acquired one or more of AMEs genes, efflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…So far, several studies have shown in vitro antibacterial and antibiofilm activity of NAC against both Gram-positive and Gram-negative microorganisms, including, amongst others, relevant difficult-to-treat pathogens such as P. aeruginosa , S. maltophilia and the Burkholderia cepacia complex [ 12 , 14 , 15 , 16 , 17 , 18 , 19 ]. More recently, Pollini et al showed a potent synergism between NAC and colistin against colistin-resistant CR-Ab, whereas no activity was observed when the strains were susceptible to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies have shown in vitro antibacterial and antibiofilm activity of NAC against both Gram-positive and Gram-negative microorganisms, including, amongst others, relevant difficult-to-treat pathogens such as P. aeruginosa , S. maltophilia and the Burkholderia cepacia complex [ 12 , 14 , 15 , 16 , 17 , 18 , 19 ]. More recently, Pollini et al showed a potent synergism between NAC and colistin against colistin-resistant CR-Ab, whereas no activity was observed when the strains were susceptible to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…Free lactoferrin and lactoperoxidase had no effect on reducing caries (Martınez-Gomis et al 1999 ). Alarfaj et al (2022) investigated the antibacterial activity of liposomes containing tobramycin and tobramycin-Nacetylcysteine. As a result, the antibacterial effect of these substances against tobramycin-resistant strains is significantly increased (Alarfaj et al 2022).…”
Section: Anti-biofilm Characteristicmentioning
confidence: 99%
“…Alarfaj et al (2022) investigated the antibacterial activity of liposomes containing tobramycin and tobramycin-Nacetylcysteine. As a result, the antibacterial effect of these substances against tobramycin-resistant strains is significantly increased (Alarfaj et al 2022). Liposomal nisin maintained inhibitory activity against biofilm production by S. mutans for up to 6 h after incubating, whilst free nisin in the same concentration inhibited biofilm production for only up to 2 h (Oho et al 2004).…”
Section: Anti-biofilm Characteristicmentioning
confidence: 99%
“…Therefore, topical tobramycin is frequently used empirically for the treatment of ocular disorders in equines [ 11 ]. Tobramycin is a broad-spectrum aminoglycoside antibiotic [ 12 ]. It has bactericidal activity mainly on gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%